2018
DOI: 10.1186/s12014-018-9198-9
|View full text |Cite
|
Sign up to set email alerts
|

CD44 glycoprotein in cancer: a molecular conundrum hampering clinical applications

Abstract: CD44 is a heavily glycosylated membrane receptor playing a key role in cell adhesion, signal transduction and cytoskeleton remodelling. It is also one of the most studied glycoproteins in cancer, frequently explored for stem cell identification, and associated with chemoresistance and metastasis. However, CD44 is a general designation for a large family of splicing variants exhibiting different degrees of glycosylation and, potentially, functionally distinct roles. Moreover, structural diversity associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 10 publications
1
52
0
Order By: Relevance
“…Building on previous insights from glycoproteomics analysis, we were then led to investigate the presence of GLUT1-STn in individual tumors. GLUT1 proteoforms, as frequently observed for other proteins in cancer [53] and have been predicted by Uniprot. Faced with these preliminary observations, we are engaging in more comprehensive glycoproteogenomics studies to fully characterize the nature of GLUT1 glycoforms in ESSC.…”
Section: Glut1 In Esccsupporting
confidence: 52%
See 1 more Smart Citation
“…Building on previous insights from glycoproteomics analysis, we were then led to investigate the presence of GLUT1-STn in individual tumors. GLUT1 proteoforms, as frequently observed for other proteins in cancer [53] and have been predicted by Uniprot. Faced with these preliminary observations, we are engaging in more comprehensive glycoproteogenomics studies to fully characterize the nature of GLUT1 glycoforms in ESSC.…”
Section: Glut1 In Esccsupporting
confidence: 52%
“…These modifications, together with difficulties in predicting the MW shift induced by glycosylation make it difficult to interpret WB singly on the MW predicted from protein amino acid sequence. Finally, we cannot exclude the expression of shorter GLUT1 proteoforms, as frequently observed for other proteins in cancer [53] and have been predicted by Uniprot. Faced with these preliminary observations, we are engaging in more comprehensive glycoproteogenomics studies to fully characterize the nature of GLUT1 glycoforms in ESSC.…”
Section: Glut1 In Esccmentioning
confidence: 90%
“…The molecular weight of CD44 largely varies among human cells, and ranges from 80 kDa to more than 250 kDa . This heterogeneity has been mainly attributed to three mechanisms, namely (a) alternative splicing at the RNA level , (b) extensive glycosylation of the protein backbone and (c) the possible proteolytic cleavage through metalloproteases at the cell surface .…”
mentioning
confidence: 99%
“…For instance, several polysaccharides such as chitosan, chondroitin sulfate, alginate, hyaluronic acid (HA) have been used to improve the active targeting of nanoparticle drug delivery systems [ 30 , 97 , 98 , 99 ]. Concerning HA, many studies have shown that HA-based nanoparticles can serve to efficiently target the CD44 glycoprotein, whose isoforms and their altered glycosylation are correlated with metastatic properties of human cancer [ 100 , 101 , 102 ]. Lastly, interesting models have been proposed and applied to various glycosylation targets, especially in combination with nanoparticle carrier systems.…”
Section: Decorating Nanoparticles Surfaces With Tacas-binding Molementioning
confidence: 99%